Peladang berpindah di Indonesia: perusak atau pengelola hutan? produksi padi dan pemanfaatan hutan Uma' jalan Kalimantan Timur - Colfer, C.J.P.; Dudley, R.G.; Hadikusumah, H.; Rusydi; Sakuntaladewi, N.; Amblani (1997)
Translation of FAO Community Forestry Case Study Series 6: Shifting cultivators of Indonesia: marauders or managers of the forest? Rice production and forest use among the Uma’ Jalan of East Kalimantan (1993). The study examines longitudinal data from four Uma’ Jalan Kenyah Dayak villages in East Kalimantan in relation to forest management issues. Shifting cultivation, rather than being ignored or rejected by scientists and policy makers, could serve as a model for developing agroforestry technologies that are appropriate for tropical rainforests. The data is used to establish trends in annual area cleared, land and forest preferences, productivity and agricultural constraints. The impacts of environmental, social structural and technological factors, natural disasters and logging on selected aspects of the agroforestry systems are also analysed. Policy issues are studies with respect to population, land use, production and tenure. Concluding policy recommendations include better control of the timber industry, acknowledgement of local people’s claims to their lands, incorporation of indigenous knowledge into agroforestry development efforts, cessation of projects which increase Kalimantan’s population and financial help for Indonesia from the community of nations to help with these efforts.